Captive [large type] - Johansen, Iris (Johansen, Iris. Eve Duncan forensics thriller., 2022)
"Eve Duncan's daughter Jane MacGuire seems to have found a perfect life with Seth Caleb--until a ruthless madman threatens to destroy it all. Jane is an internationally renowned artist, while Seth channels his unique abilities as an agent for the MI6 intelligence service. But when Seth crosses crime lord Hugh Bohdan, he incurs the wrath of one of the world's most powerful criminal empires... one whose tentacles reach across the globe and even to the idyllic Scottish retreat where Jane is working. Soon Jane is on the run, struggling to stay one step ahead of Bohdan's army and devastating high-tech weaponry. Even with the assistance of Scottish Earl John MacDuff, she finds danger at every turn. But with that peril comes an astonishing discovery: a 200-year-old secret on the brink of becoming lost to history. Together Jane and Caleb must join forces to unlock the fascinating puzzle, even as they hurtle toward a lethal final confrontation in the Scottish Highlands. The suspense builds with each twist and turn... and before their adventure is over, Jane and Caleb will encounter their biggest shock of all... and realize nothing can be the same for them ever again"--